Rifampicin-resistant Tuberculosis and Associated Factors Among Pulmonary Tuberculosis Patients in Mahakali Provincial Hospital, Nepal - Bohara, Madan Singh; Ojha, Ramesh Chandra (Far Western Review, 2024)
The study aims at assessing the prevalence of RR-TB and identify associated factors among pulmonary TB patients using GeneXpert MTB/RIF assay data from January to December 2023. Tuberculosis (TB) continues to pose a significant global health threat, with rifampicin-resistant (RR) strains presenting a formidable challenge to disease control efforts. This study based the retrospective cross-sectional study conducted at Mahakali Provincial Hospital in Nepal. Out of 2587 presumptive TB cases, 11.8% were confirmed positive for TB, with males constituting a significantly higher proportion (66.1%) than females (33.9%). Among TB-positive cases, 3% showed resistance to rifampicin, predominantly affecting males (77.8%). Age group analysis revealed higher TB detection rates in the 46-60 years group, while rifampin -resistance tuberculosis (RR-TB) cases were more evenly distributed across age groups without statistical significance. Ethnicity and residential locality did not show significant associations with RR-TB. Multivariate logistic regression highlighted gender as RR-TB and associated factors among pulmonary tuberculosis patients in a Mahakali Provincial Hospital, Nepal. Rifampicin-resistant TB (RR-TB) remains a significant challenge at Mahakali Provincial Hospital, with a 3% prevalence, predominantly affecting males. Gender is a key factor in RR-TB prevalence. To manage and reduce RR-TB effectively, it is necessary to implement targeted interventions for high-risk groups, particularly males, and to enhance diagnostic capabilities.